Facile solvothermal synthesis of NiFe2O4 nanoparticles for high-performance supercapacitor applications - Sethi, Meenaketan; Shenoy, U. Sandhya; Muthu, Selvakumar; Bhat, D. Krishna (Frontiers of materials science, 2020)
We report a green and facile approach for the synthesis of NiFe 2 O 4 (NF) nanoparticles with good crystallinity. The prepared materials are studied by various techniques in order to know their phase structure, crystallinity, morphology and elemental state. The BET analysis revealed a high surface area of 80.0 m 2 ·g −1 for NF possessing a high pore volume of 0.54 cm 3 ·g −1 , also contributing to the amelioration of the electrochemical performance. The NF sample is studied for its application in supercapacitors in an aqueous 2 mol·L −1 KOH electrolyte. Electrochemical properties are studied both in the three-electrode method and in a symmetrical supercapacitor cell. Results show a high specific capacitance of 478.0 F·g −1 from the CV curve at an applied scan rate of 5 mV·s −1 and 368.0 F·g −1 from the GCD analysis at a current density of 1 A·g −1 for the NF electrode. Further, the material exhibited an 88% retention of its specific capacitance after continuous 10000 cycles at a higher applied current density of 8 A·g −1 . These encouraging properties of NF nanoparticles suggest the practical applicability in high-performance supercapacitors.